2014
DOI: 10.1186/1880-5981-66-94
|View full text |Cite
|
Sign up to set email alerts
|

Vertical coupling of atmospheres: dependence on strength of sudden stratospheric warming and solar activity

Abstract: Comprehensive behavior of the low-latitude upper atmosphere during sudden stratospheric warming (SSW) events at varying levels of solar activity has been investigated. The equatorial electrojet (EEJ) strength and the total electron content (TEC) data from low latitudes over Indian longitudes during the mid-winter season in the years 2005 to 2013 are used in this study. Five major and three minor SSW events occurred in the observation duration, wherein the solar activity had varied from minimum (almost no sunsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…Mthembu et al (2013) found notable variability of the semidiurnal tide due to interactions with planetary waves of periods $ 5, 6, 23 days. Most recent study by Laskar et al (2014) observed considerable interaction between the semidiurnal tide and quasi-16-day wave during major sudden stratospheric warming and solar maximum condition. Although a number of studies have been carried out both theoretically and observationally aiming at understanding the underlying processes responsible for the tide-planetary wave interactions from various locations over the globe, our knowledge is very limited so far, especially related to the southern hemisphere, where planetary wave activities are weaker as compared to the northern hemisphere as well as least available observational studies.…”
Section: Introductionmentioning
confidence: 98%
“…Mthembu et al (2013) found notable variability of the semidiurnal tide due to interactions with planetary waves of periods $ 5, 6, 23 days. Most recent study by Laskar et al (2014) observed considerable interaction between the semidiurnal tide and quasi-16-day wave during major sudden stratospheric warming and solar maximum condition. Although a number of studies have been carried out both theoretically and observationally aiming at understanding the underlying processes responsible for the tide-planetary wave interactions from various locations over the globe, our knowledge is very limited so far, especially related to the southern hemisphere, where planetary wave activities are weaker as compared to the northern hemisphere as well as least available observational studies.…”
Section: Introductionmentioning
confidence: 98%
“…An event is considered as “major” if in addition to increased temperatures, zonal mean eastward winds reverse at these altitude and latitude regions [ McInturff , ; Labitzke , ]. SSW is attributed to the interaction of zonal winds with vertically propagating planetary waves (PWs) forced from the troposphere, and their effect in terms of quasi 16 day waves has also been seen to be present over low‐ and equatorial‐latitude E and F regions of the ionosphere [e.g., Laskar et al , ]. It has also been shown that the westward acceleration of zonal winds over northern hemispheric high latitudes occurs during SSW periods in the presence of PWs [ Matsuno , ].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of quasi 16 day periodicity around the NE stations suggests that the ionization over NE stations do not get influenced by the EEJ and the consequent fountain effect. The earlier workers also reported the presence of quasi 16 day wave during the SSW events at the low‐latitude ionosphere of the Indian zone, which are linked with the changes in the equatorial electric fields (Laskar et al, ; Patra et al, ; Sripathi & Bhattacharyya, ). The presence of quasi 16 day wave during the SSW event of 2013 was also observed over midlatitude ionosphere (Chen et al, ).…”
Section: Discussionmentioning
confidence: 93%